Tracing Back the Radiance : Chinul's Korean Way of Zen - Buswell, Robert E. (University of Hawaii Press, 1991)
Chinul (1158-1210) was the founder of the Korean tradition of Zen. He provides one of the most lucid and accessible accounts of Zen practice and meditation to be found anywhere in East Asian literature. Tracing Back the Radiance, an abridgment of Buswell#x92;s Korean Approach to Zen: The Collected Works of Chinul, combines an extensive introduction to Chinul#x92;s life and thought with translations of three of his most representative works.